AB0019 Comparison of IL-23 Receptor Gene Polymorphisms in Patients with Primary Sjögren Syndrome, Ankylosing Spondylitis, and Ankylosing Spondylitis with Sjogren's Syndrome. (9th June 2015) - Temel, S.; Balkarli, A.; Tepeli, E.; Cobankara, V.
Abstract : Background: There are many studies about the association between AS and IL-23 receptor gene polymorphism. It is known that the frequency of SS increase in AS patients. There is not any study that evaluates the association between patients that have both AS and SS and IL-23R gene polymorphism. Objectives: We studied the possible association of IL-23 receptor gene polymorphisms in patients with Primary Sjögren syndrome, Ankylosing spondylitis, and Ankylosing spondylitis with Sjogren's syndrome. Methods: 124 AS, 55 SS, 12 both AS and SS and 96 healthy controls recruited for this study. IL-23 gene, rs11805303, rs10889677, rs1004819, rs2201841, rs11209032, rs7530511, rs11209026, rs10489629, rs7517847 variants were studied by PCR-RFLP method. Results: rs10889677 gene mutant genotype frequency was statistically higher and rs11209032 gene mutant genotype frequency was statistically less in A.S. group compared with healthy controls (p=0, 023, p<0, 001). Both of rs2201841 and rs11805303 gene wild genotype frequency was statistically higher in SjS group compared with healthy controls (p<0, 001, 0, 009), rs11209032 gene heterozygous and rs10489629 gene mutant genotype frequency was statistically less in SS group compared with healthy controls (p<0, 001, 0, 003). In the group of patients with AS and SS rs11209032 gene wild genotype frequencies were significantly increased compared to the control group (p<0, 001). rs11805303 and rs10489629 gene mutant genotype frequencies were significantly increased in AS group compared to the SS group, but in the group of patients with SS; rs10889677 gene heterozygous, rs2201841 gene wild and rs11209032 gene mutant genotype frequencies were significantly increased compared to the AS group. In the group of patients with AS and SS rs11209032 gene wild genotype frequencies were significantly increased compared to the AS group (p=0, 049). In the group of patients with AS and SS; rs11805303 gene mutant, rs11209032 gene wild, rs10489629 gen mutant genotype frequencies were significantly increased compared to the SS group (p<0, 05). Although rs10889677 gene mutant genotype can be interpreted as predisposition of AS, rs11209032 gene mutant genotype can be protective from AS. There is only one study about IL-23 gene polymorphism in SS patients in literature and no relationship was found. In the group of patients with SS; rs11805303 gene wild genotype and rs2201841 gene wild genotype frequencies were significantly increased, but rs11209032 gene heterozygous genotype and rs10489629 gene mutant genotype decreased compared to the control group. Conclusions: According to our results we have found both rs11805303 gene wild genotype and rs2201841 gene wild genotype can predispose to SS and rs11209032 gene heterozygous genotype and rs10489629 gene mutant genotype protect from SS. rs11209032 gene mutant and heterozygous genotype frequencies which interpreted as protective from AS and SS were significantly decreased in the group of AS and SS patients compared to the AS group, but wild gentoype frequencies were increased. These results of rs11209032 genotype wild gene may be associated with the development of SS in patients with AS. Genotype distribution and genetic diversity varies between ethnic groups. Disclosure of Interest: None declared